Analysis of Groundwater Quality for Clean Water Supply in Pasaran Island, Bandar Lampung City, Indonesia - Maryadi Budi Wiyono; Tjahyo Nugroho Adji (Forum Geografi, 2021)
Pasaran is the only productive small island functioning as the anchovy and green clam production center in Bandar Lampung. Its water use has, however, increased since its designation as an economically fishery-based development area or minapolitan in 2012. This is due to the fact that groundwater resources in small island ecosystems surrounded by seawaters with a narrow diameter are easily affected by the insistence of seawater. Moreover, population pressure and land-use change are also feared to be affecting groundwater quality. Therefore, this research was conducted to analyze and evaluate groundwater resource quality in Pasaran Island using five wells on the entire island as sampling points selected based on census. The samples were tested for physical, chemical, and biological parameters in the laboratory and compared with water quality standards (Minister of Health’s Regulation No. 32/2007). The results showed relatively low water quality because the samples contained up to 3900 μS/cm salinity, 3771.9 mg/l chlorides, 31.7–141.52 mg/l nitrates, and 6.8–170 MPN/100ml total coliform which exceed the standards for drinking water. Meanwhile, wells 1, 4, and 5 were found to be safe for sanitation-hygiene purposes and well 1 was suitable for public baths even though they are not of drinking quality. This means the groundwater quality generally met Class II-water requirements for clean water supplies.